Development of Electronic Student Worksheets (E-LKPD) Based on Discovery Learning for Chemistry Material for High School Students - Weslita Sitohang; Ajat Sudrajat (Pascasarjana, Mataram University, 2026)
In chemistry learning, the application of technology, experimental activities, case studies, class discussions, and direct involvement in the application of concepts play a crucial role. Students struggle to understand chemistry material not only due to a lack of teacher skills but also due to the teachers' limited resources. The purpose of this research was to determine the needs analysis, feasibility level, and teacher and student responses to the discovery learning-based E-LKPD on acid-base material. This type of research is a Development Research (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) but the implementation was only carried out up to the development phase. The subjects of this study included Material Experts, Media Experts, and chemistry teachers, grade XII Bio 1 students. The results of the study proved that the discovery learning-based E-LKPD that had been developed obtained a feasibility percentage of 86% from the material experts, which was included in the very feasible criteria, and 87% from the media experts, which was included in the very feasible criteria. Chemistry teachers' responses to the developed e-LKPD also showed positive results, with 94% categorizing it as very appropriate. Meanwhile, students' responses to the discovery learning-based e-LKPD were categorized as very interesting at 90%. Based on these results, the developed e-LKPD was deemed appropriate and met the criteria for use in the chemistry teaching and learning process for acids and bases.